Effects of Surface Chemical Structure on the Mechanical Properties of Si1-xGex Nanowires - Ma, J. W.; Lee, W. J.; Bae, J. M.; Jeong, K. S.; Kang, Y. S.; Cho, M. -H.; Seo, J. H.; Ahn, J. P.; Chung, K. B.; Song, J. Y. (AMER CHEMICAL SOC, 2013)
The Young's modulus and fracture strength of Si1-xGex nanowires (NWs) as a function of Ge concentration were measured from tensile stress measurements. The Young's modulus of the NWs decreased linearly with increasing Ge content. No evidence was found for a linear relationship between the fracture strength of the NWs and Ge content, which is closely related to the quantity of interstitial Ge atoms contained in the wire. However, by removing some of the interstitial Ge atoms through rapid thermal annealing, a linear relationship could be produced. The discrepancy in the reported strength of Si and Ge NWs between calculated and experimented results could be related to SiO2-x/Si interfacial defects that are found in Si1-xGex NWs. It was also possible to significantly decrease the number of interfacial defects in the NWs by incorporating a surface passivated Al2O3 layer, which resulted in a substantial increase in fracture strength.
Keywords: FIELD-EFFECT TRANSISTORS; GERMANIUM NANOWIRES; SILICON NANOWIRES; SUPERLATTICES; PERFORMANCE; STRENGTH; HETEROSTRUCTURES; OPTOELECTRONICS; SPECTROSCOPY; TEMPERATURE